Comparison of New‐Onset Peripheral Artery Disease in Patients With Type 2 Diabetes Exposed to Sodium–Glucose Cotransporter‐2 Inhibitors, Dipeptidyl Peptidase‐4 Inhibitors, or Glucagon‐Like Peptide‐1 Agonists: A Population‐Based Cohort Study - Oscar Hou‐In Chou; Zhiyao Luo; Cheuk To Skylar Chung; Jeffrey Chan; Huixian Li; Ishan Lakhani; Sharen Lee; Dawnie Ho Hei Lau; Qingpeng Zhang; Tong Liu; Wing Tak Wong; Bernard Man Yung Cheung; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Sodium‐glucose cotransporter‐2 inhibitors (SGLT2Is), dipeptidyl peptidase‐4 inhibitors (DPP4Is), and glucagon‐like peptide‐1 receptor agonists have been associated with improved cardiovascular outcomes and prognosis. The comparative risks of new‐onset peripheral artery disease (PAD) between these medications remain unknown. This real‐world study compared the risks of PAD in patients exposed to SGLT2I and DPP4I. METHODS AND RESULTS This was a retrospective population‐based cohort study of patients with type 2 diabetes on either an SGLT2I or a DPP4I between January 1, 2015, and December 31, 2015, using a territory‐wide database from Hong Kong. The primary outcome was new‐onset PAD. The secondary outcomes were cardiovascular hospitalization, cardiovascular death, and all‐cause death. Propensity score matching (1:1 ratio) using the nearest neighbor search was performed. Multivariable Cox regression with time‐weighted variables was used to identify significant associations. A 3‐arm analysis including the glucagon‐like peptide‐1 receptor agonist cohort was conducted. This cohort included 75 470 patients with type 2 diabetes (median age, 62.3±12.8 years; 55.79% men). The SGLT2I and DPP4I groups consisted of 28 753 patients and 46 717 patients, respectively. After matching, 186 and 256 patients had PAD in the SGLT2I and DPP4I groups, respectively, over a median follow‐up of 5.6 years. SGLT2I use was associated with lower risks of PAD (hazard ratio [HR], 0.79 [95% CI, 0.66–0.93]) compared with DPP4I use after adjusting for demographics, comorbidities, medications, renal function, and glycemic tests. The association remained consistent regardless of sex, age, and other metabolic diseases. In the 3‐arm analysis, the risk of PAD was not statistically different between SGLT2Is and glucagon‐like peptide‐1 receptor agonists (HR, 1.18 [95% CI, 0.52–2.68]). The results remained consistent in the competing risk and the sensitivity analyses. Conclusions SGLT2I use among patients with type 2 diabetes was associated with lower risks of new‐onset PAD and PAD‐related outcomes when compared with DPP4Is after adjustments.